1759–1773: The suppression of the society of Jesus - Serrão, J. V. (The global history of Portugal: From prehistory to the modern world, 2022)
The suppression of the Society of Jesus – a political process that was transnational in nature and global in its effects – began in Portugal and was led by the powerful Marquis of Pombal, chief minister of King Joseph I.